Analisis Asas Ijarah pada Sistem Pengupahan Sales di Kecamatan Banjaran - Said, Syakirah Apriliahana; Relit Nur Edi; Anis Sofiana (Al-'Adl, 2025)
This study explores the application of the ijarah principle in the wage system for sales workers in Banjaran District, focusing on assessing justice ('adl) and worker protection. The research aims to evaluate whether the commission-based wage system implemented in small-scale toy businesses aligns with the principles of ijarah contracts in Islamic law. Using a descriptive-analytical qualitative approach, data were collected through interviews, observation, and documentation. The findings indicate that the wage system formally meets essential elements of ijarah, including clear contracts and mutual consent. However, substantive justice and worker protection are not fully achieved, as workers bear economic risks without a guaranteed minimum income. This study proposes a reform of the ijarah-based wage model by integrating income guarantees and risk-sharing mechanisms in accordance with the maqāṣid al-sharī'ah. These findings are expected to contribute to the development of a fairer wage system in Sharia-compliant employment relations